Cambial growth periodicity studies of south american woody species-a review - Henriques Callado, Cátia (2013)
This paper reviews histological studies of cambium activity in South American woody species and provides future research prospects. The majority of the studies almost exclusively describe radial increment and/or its periodicity. There are 15 papers concerning the cambial activity of 17 woody species from the South American flora and 3 exotic species in 4 countries that were published to date. Despite endogenous factors affecting the radial meristem, the seasonality of rains has been identified as the main factor influencing cambial activity in the tropics and subtropics. There is a lack of standardization and a need for improvement and discussion concerning the methods used. Moreover, radial growth studies conducted by monitoring cambium cell production are still scarce in South America, especially when considering the high diversity of the continent's flora and ecosystems.